Tidal range influence on fish assemblages in a Brazilian tropical estuary - Batista, Vandick da Silva; Rêgo, Frederico Nunes (Arquivos de Ciências do Mar, 2017)
The tidal influence on the fish assemblage of creeks in the Tibiri River estuarine zone, Maranhão State, Brazil was investigated using a 120-m barrier net. A linear model showed the best fit to the data of diversity against tidal range, but it did not predict well the diversity on days with a tidal range lower than 2.8 m, when it ranged from 0.25 to 1.1 bit with a mean about 32% lower than days with a tidal range over 2.9 m. The number of individuals and biomass was not affected by the tidal range. Different volumes of water and turbidity are the causes of differences in diversity. The most representative results in terms of species diversity may be obtained in days of tide equal or greater than 2.9 m. For comparative purposes, samples must be taken during days of similar tidal range excluding those in the range 2.8 - 2.9 m and preferably at about the same daytime.